COVID-19: Analysis of Factors Affecting the Economy of Hunan Province Based on the Spatial Econometric Model - Pan, Wen-Tsao; Zhonghuan, Wu; Shiqi, Chen; Siyi, Xiao; Yanping, Tang; Danying, Liang (Frontiers in Public Health, 2022)
The COVID-19 pandemic has spread across the country negatively impacting on the economy. This paper uses the panel data of 14 prefecture-level cities from 2015 to 2020 in Hunan to determine the factors and effects of economic downturns based on the spatial econometric model. We calculate the Moran index, so-called the Moran's I, to analyse the impact of each factor on the economy. The results show that the spatial correlation of the cities around Chang-Zhu-Tan is high, and the economic growth of the entire province can be influenced by these cities. These cities should adopt strategies to improve the economy, such as reducing the tax revenues, improving the local financial revenues, and reducing the ineffective educational input. These results can also be helpful for policymakers, who will attempt to retransform the Hunan economy during the post-COVID era.